The Growth of Apprenticeship in England: Doubts Beneath the Numbers. Issue 5 (2nd September 2016) - Fuller, Alison
Abstract : England is investing aggressively in its apprenticeship system. Indeed, it has been expanded significantly. But while some of these programs are effective, the author is concerned that they don't emphasize learning skills adequately. This becomes epically relevant now that there is a new levy on business to support an expanded apprenticeship system.